A novel a-Si PV/T solar cogeneration system using the coupled thermal storage/ORC as an alternative to battery - Kutlu, Cagri (2020)
The recent intensive focus on energy and environmental issues has resulted in an increase in studies of renewable energy applications. Solar energy has been identified as one of the most promising types, with solar energy technologies attracting a high level of interest in order to satisfy current energy demands. It is known that solar heat collection usually has a low to medium temperature in comparison with combustion heat in steam power plants. Therefore, the Organic Rankine Cycle (ORC) is appropriate for the generation of electricity from solar heat. By using the solar ORC system with a heat storage unit, electricity generation can continue during the night, however, it is known that solar to electricity conversion efficiency of these systems is low. Photovoltaic (PV) technology has become a popular technology in recent years for electricity generation; however, electricity conversion efficiencies of this technology are still relatively low, resulting in a large proportion of collected solar radiation being dissipated as heat. To utilise this heat dissipation for other purposes, photovoltaic/thermal (PV/T) technology has become a very attractive option for solar-driven combined heat and power systems. Heat from a PV/T system can be used directly or stored for use at other times to drive a power generation cycle. The main problem with the low to medium temperature PV/T system is its lower electricity conversion efficiency at a raised temperature. However, this problem can be solved by using amorphous silicon (a-Si) PV cells instead of crystalline silicon cells. This thesis aims to investigate the potential and characteristics of a PV/T system coupled with thermal storage, using the ORC as an alternative to battery in matching the energy demand profile of buildings. In order to carry out the investigations, a thermodynamic analysis of the combined system is presented, including the transient modelling of a hot water storage tank. Components were modelled considering off-design operation in transient state associated with hourly EnergyPlus weather data. After completion of the modelling, a detailed experimental investigation was conducted, with a focus on the performance of a scroll expander, as the most critical component of the ORC, its operation metrics and performance. As the key factor is matching the user electricity demand profile, this thesis further uses a controlling methodology for the solar ORC system to control electricity output according to this profile. By adopting this methodology, the collected and stored solar heat can be utilized more effectively, thus allowing for the provision of high electricity output for users during peak hours. The thesis comprises a literature review of the whole system’s components and presents a detailed modelling of a solar ORC system, considering both daily and annual electricity demand profiles of residents. Additionally, it investigates the direct incorporation of a solar organic Rankine cycle with a vapour compression refrigeration unit to reduce electricity conversion losses. Finally, the modelling of a scroll expander is comprehensively conducted; expander generator coupling performance is assessed and a realistic modelling methodology is presented. Results show that it is possible to meet the electricity demand even at night by controlling the mass flow rate of the circulation water. In order to provide 24-hour electricity to a small community with twelve dwellings, 550 m2 collector area and 88 m3 heat storage unit are required for a solar ORC system. Solar energy to electricity conversion ratio was found quite low for the solar ORC systems, but for proposed innovative a-Si PV/T-ORC system, electricity generation is increased 103 % compared to solar ORC system for operations in July. a-Si PV/T-ORC system also integrated with a vapour compression system to provide both electricity and cooling. Results show required solar collector area and heat storage unit reduce considerably by adapting PV/T-ORC-VCC unit. Finally, new scroll expander-generator coupling modelling approach allows users to predict rotational speed and electricity output.